A produção escrita em língua inglesa nas interfaces papel e blog - Kozilkoski, Elisabeth Pacheco Lomba (2007)
This research aimed at (1) identifying the representations high school students reveal about writing in English when paper and blog are used as writing interfaces, and (2) describing and interpreting the process of writing in English on paper and blog as a phenomenon of lived experience. To reach these pre-established goals, this study was theoretically grounded on developments in CAI and CALL (Warschauer, 1998; Garret 1991, Ponte, 1992; Towers, 1992; Brave, 1993); on the concept of blog as interface and on its use in the educational area (Haag, 2006; Williams & Jacobs, 2004; Lara, 2005; O'Donnell, 2005, among others), and on the guidelines presented by the PCN regarding the utilization of technological resources for instructional purposes. The methodological approach was the hermeneutic-phenomenological one (van Manen, 1990). The research context was a public school of São Paulo countryside, and it involved 28 high school students and myself, the teacher/researcher. The texts collected were qualitatively interpreted, considering the identification of recurrent themes (van Manen, 1990), made explicit through a refinement process (Freire, 2006, 2007), which consolidated the validating cycle (van Manen, 1990). The results indicated that the participants representations about writing in English by using the two interfaces focused on in this study were different, thus revealing that, from the students perspective, writing in English on paper was somehow different from blogging. The outcomes also revealed that the structure of the process of writing in English on paper and on blog was different, thus indicating that, in fact, we were dealing with two phenomena of human experience, and not with a single one, as assumed initially. This dissertation aims at contributing to the reflective educational practice of those teachers who intend to develop the written production in English by using blogs, and who look not only for the written product but mainly for writing as a process